2006
DOI: 10.1089/ten.2006.12.1357
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Drug Metabolism Activities of C3A— A Human Hepatocyte Cell Line—By Tissue Engineering Within Alginate Scaffolds

Abstract: In this study, we investigated the applicability of C3A--a human hepatocyte cell line--as a predicting tool for drug metabolism by applying tissue-engineering methods. Cultivation of C3A cells within alginate scaffolds induced the formation of spheroids with enhanced drug metabolism activities compared to that of two-dimensional (2-D) monolayer cultures. The spheroid formation process was demonstrated via histology, immunohistochemistry, and transmission electron microscope (TEM) analyses. The C3A spheroids di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 17 publications
6
67
0
2
Order By: Relevance
“…22,23 Interestingly, we have also shown that hESC-DE cells behave differently from HepG2 cells when cultured in an Algimatrix 3D scaffold. Firstly, hESC-DE cells required the treatment of ROCKi to survive in the 3D culture after dissociation, whereas HepG2 cells do not require ROCKi to survive or to form spheroids.…”
Section: Discussionmentioning
confidence: 81%
“…22,23 Interestingly, we have also shown that hESC-DE cells behave differently from HepG2 cells when cultured in an Algimatrix 3D scaffold. Firstly, hESC-DE cells required the treatment of ROCKi to survive in the 3D culture after dissociation, whereas HepG2 cells do not require ROCKi to survive or to form spheroids.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, CYP3A4 activity in the encapsulated HLC was close to that of encapsulated HepG2 cells. Previous studies reported elevated CYP3A4 activity in hepatocytes grown on matrices or encapsulated to create a three-dimensional environment [45][46][47], and that the increase in CYP3A4 activity could be due to increased cell to cell contact, additional extracellular matrix and recovery of cell polarity within in the microcapsule [44,48]. Thus, encapsulated HLC may also be suitable as an in vitro drug screening tool.…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 99%
“…34 Therefore, it is important to conserve the ability of hepatocytes to synthesize albumin in a HF-based BLAD. The reported albumin synthesis rates for human hepatoma/immortalized hepatocytes (HepG2/C3A/HepLL) ranged from 0.0625 to 0.42 mg/h/10 6 cells [35][36][37][38] ; primary human hepatocytes ranged from 0.002 to 0.006 mg/h/10 6 cells 39 ; primary porcine hepatocytes ranged from 0.05 to 6.6 mg/h/10 6 cells 30,[40][41][42] ; and primary rat hepatocytes ranged from 0.2 to 0.4 mg/h/10 6 cells. 43 The capacity for albumin synthesis in our experimental HF bioreactors with C3A cells (0.4-0.8 mg/h/10 6 cells) is comparable or even higher than most of the aforementioned primary cells and cell lines derived from various sources.…”
Section: Biosynthetic Functionmentioning
confidence: 99%